An exploratory study of governance practices at the student, Institutional, and Systems level of selected Higher Education Institutions in South Africa - Brown, Tom Mark (Stellenbosch : Stellenbosch University, 2025)
Thesis (PhD)--Stellenbosch University, 2024.